Representations of translators and translation in Japanese fiction - Wakabayashi, Judy (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper examines some 40 Japanese fictional works containing portray-als of translators or translation (here understood as including interpreting). It explores Japanese writers’use of translation as a metafictional device, the extent to which these works (mis)represent reality, whether they are positive or negative depictions, and the insights they provide into how translators and translation are regarded by Japanese authors and, by extension, the Japanese public. Recurring themes are analyzed, such as marginality and identity issues, power and fidelity, author/translator relations, attitudes toward translators, and translation as a profession and business. Of par-ticular interest is the question of how Japanese depictions might differ from those by Anglo-American writers.